SEVERAL ISSUES AND DIRECTIONS IN THE STUDY OF NOMADIC STATEHOOD (Journal of history, 2019)
This is a brief historiographical overview on the literature regarding the Kazakh Khanate against the backdrop of nomadism. This study is relevant due to the need of an objective and complex analysis of issues surrounding the history of the Kazakh Khanate, especially with regards to statehood within the context of a nomadic society. That is why this article examines several works on the issues of statehood in nomadic societies. While interest in nomadic societies has not diminished, the question remains on how to present the issues in a deep and objective manner. In this regard, this article analyzes the works of scholars who have studied the fundamental questions of this topic, including those who have looked into the definition of statehood, its etymology, signs, elements; the various forms of states, the origins of states and their functions, political regimes, authority and social norms, as well as other aspects.